TINJAUAN HUKUM ISLAM TERHADAP HAK PEREMPUAN DALAM MEMILIH PASANGAN HIDUP: Studi Kasus di Desa Dolago Padang Kecamatan Parigi Selatan Kabupaten Parigi Moutong - Rahmadani; Jumat, Gani; Mursyid, Besse Tenriabeng (Program Studi Perbandingan Mazhab, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2023)
Islam provides women with rights under the Prophet Muhammad SAW. With the changes, women have full freedom of ownership rights in all permitted ways and have full rights to express opinions when they are asked to express their opinions. This research uses sociological research methods on law using empirical data collected through techniques. observation, interviews and documentation, the data analysis techniques used are data reduction, data presentation and checking the validity of the data. From women's opinions regarding the implementation of women's rights in choosing a life partner, not all implementations of women's rights have been implemented because they are still held by those closest to them. Therefore, the importance of communication and education in determining life choices. As the Hanafi school of thought emphasizes that women have the right to choose. The Prophet also said